Whistleblowing and Payroll Fraud Control in Public Sector - Oton, Ovat Raymond; Effiong, Sunday A (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2026)
Purpose: This study examined the influence of whistleblowing mechanisms on payroll fraud control in the Nigerian public sector, with particular emphasis on the reduction of ghost workers and multiple salary payments. The study specifically investigated the effects of anonymous whistleblowing and internal whistleblowing on payroll fraud control. Methodology: A survey research design was adopted. The study was conducted among employees involved in payroll administration, internal auditing, human resource management, and related administrative functions in selected public institutions in South-South Nigeria. A purposive sampling technique was used to select 210 respondents. Data were collected through structured questionnaires and analyzed using descriptive statistics, Pearson correlation, and multiple regression analysis with the aid of the Statistical Package for Social Sciences (SPSS). Results and Conclusion: The findings revealed that anonymous whistleblowing has a positive and statistically significant effect on payroll fraud control (β = 0.512, p < 0.05), while internal whistleblowing also exerts a significant positive influence (β = 0.376, p < 0.05). The regression model explained 61% of the variation in payroll fraud control (R² = 0.610), indicating that whistleblowing mechanisms are important predictors of fraud control effectiveness. The study concludes that effective whistleblowing systems enhance payroll accountability and contribute significantly to the reduction of payroll fraud in public institutions. Implication of Findings: The findings underscore the need for public institutions to strengthen confidential reporting mechanisms and institutional support systems that encourage employees to report payroll irregularities without fear of victimization.